2016
DOI: 10.1002/jms.3805
|View full text |Cite
|
Sign up to set email alerts
|

The photobase generator nifedipine as a novel matrix for the detection of polyphenols in matrix-assisted laser desorption/ionization mass spectrometry

Abstract: Matrix assisted laser desorption/ionization mass spectrometry (MALDI-MS) is widely used for the detection and analysis of ionizable compounds. However, the method has less potential for the analysis of neutral compounds, such as polyphenols, owing to their lack of favorable proton-attachment or -removal groups. In this study, we reported for the first time that nifedipine (2,6-dimethyl-3,5-dicarbomethoxy-4-(2-nitrophenyl)-1,4-dihydropyridine), which is a strong photobase generator commonly used in polymerizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…To visualise the in situ absorption behaviour of polyphenols using MALDI-MSI, nifedipine was used as the preferred matrix reagent, together with other common matrix reagents. Our previous studies showed that nifedipine enhanced the ionisation of less-ionisable polyphenols (e.g., flavonols, flavones, flavanones, flavonones, chalcones, stilbenoids, and phenolic acids), by removal of a proton from the polyphenol skeleton due to its photobase properties 20 .…”
Section: Introductionmentioning
confidence: 99%
“…To visualise the in situ absorption behaviour of polyphenols using MALDI-MSI, nifedipine was used as the preferred matrix reagent, together with other common matrix reagents. Our previous studies showed that nifedipine enhanced the ionisation of less-ionisable polyphenols (e.g., flavonols, flavones, flavanones, flavonones, chalcones, stilbenoids, and phenolic acids), by removal of a proton from the polyphenol skeleton due to its photobase properties 20 .…”
Section: Introductionmentioning
confidence: 99%
“…(36) However, the MALDI-MS detection of polyphenols, which have neutral chemical structures (except for anthocyanins, which have positively charged flavylium skeletons), has severe limitations owing to their lack of proton removal or addition groups. (37) Moreover, there are several limitations for the aforementioned conventional matrices, such as an abundance of interfering signals in the low-mass range for a positive detection mode and a low ionization efficiency for a negative detection mode. (36) Several attempts at detecting polyphenols by MALDI-MS have been reported in the literature, as listed in Table 1.…”
Section: Matrix Selection For Maldi-ms Visualization Of Polyphenolsmentioning
confidence: 99%
“…(37) The mechanism of nifedipine-induced MS ionization of polyphenols involves the production of a nitrosophenyl pyridine derivative from nifedipine under laser irradiation at 355 nm. (37) This photobase product plays a crucial role in the deprotonation of polyphenols in negative-mode MALDI-MS [as illustrated in Fig. 2(b)].…”
Section: Matrix Selection For Maldi-ms Visualization Of Polyphenolsmentioning
confidence: 99%
See 2 more Smart Citations